The Association between the Preference for Active Play and Neurological Development in Toddlers: A Register-Based Study - Pakarinen A; Hautala L; Hamari L; Aromaa M; Kallio H; Liuksila PR; Sillanpää M; Salanterä S (Switzerland, 2025)
Active play is regarded as physical activity during early childhood. Physical activity has many benefits for children’s physical and psychosocial health and wellbeing, as well as for their cognitive development. The aim of this study was to investigate associations between the preference for active play and neurological development in toddlers. The study was conducted as a register-based study, and the data were collected from a public-health clinic’s electronic health records. The register data about active play used in this study were originally assessed by parents at home and by early years teachers at nurseries. Neurological development was assessed by the public health nurses in public child-health clinics. The data eligible for this study were available from 717 toddlers aged 2.5–3.0 years old (mean: 2.5 years ± 2 months). The majority of toddlers (85%) showed a preference for active play, both at home and at the nursery. The prevalence of delays in the neurological development of toddlers varied in different developmental areas (by 1–15%). Delays in gross motor competence, auditory perception, and self-help skills were associated with a lower preference for active play in nursery settings, but none of the neurodevelopmental items were found to be associated with toddlers’ preference for active play at home. Nurseries need to encourage children to actively play and support their gross motor competence and self-help skills.